2017
DOI: 10.1007/s10508-017-0987-4
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Associated Factors Among Gay and Heterosexual Male University Students in Nigeria

Abstract: Homosexuality is a recognized risk factor for depression in high-income countries; however, there is little research investigating the relationship between depression and sexual orientation in developing countries, especially in Africa. In this first study to investigate psychopathology in sexual minority men in Nigeria, the prevalence rates of depression in Nigerian gay and heterosexual individuals were compared as well as the explanatory power of risk and resilience factors in both groups. Eighty-one gay and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Needham and Austin ( 2010 ) 1 1 1 1 0 0 0 0 1 1 1 0 Fair 23. Oginni et al 2018 1 1 0 0 1 0 0 0 1 1 0 1 Fair 24. Pakula et al ( 2016 ) 1 1 0 0 0 1 0 0 1 1 1 0 Fair 25.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Needham and Austin ( 2010 ) 1 1 1 1 0 0 0 0 1 1 1 0 Fair 23. Oginni et al 2018 1 1 0 0 1 0 0 0 1 1 0 1 Fair 24. Pakula et al ( 2016 ) 1 1 0 0 0 1 0 0 1 1 1 0 Fair 25.…”
Section: Resultsmentioning
confidence: 99%
“…(α = .83 for the current residential mother support scale, α = .74 for the current residential father support scale, α = .86 for the previous residential mother support scale, and α = .89 for the previous residential father support scale) 23. Oginni et al (2018) Age: M = 25. Family relationships: Items asking questions about each of the respondents' relationship with their parents, e.g., "How close do you feel to your mother/father?".…”
Section: Study Sample Characteristicsmentioning
confidence: 99%
“…Nigerian gay, bisexual, and other men who have sex with men (GBMSM) experience marginalization, discrimination and violence due to their sexual orientation and same-sex sexual activity [1][2][3], which may negatively impact physical, mental, and sexual health outcomes [4,5]. The minority stress model posits that the prejudice, discrimination, and stigma experienced by sexual and gender minority individuals-as a result of sexual or gender identity-contributes to higher levels of stress, which may lead to mental health problems [6] and sexual risk behaviors [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nigerian gay, bisexual, and other men who have sex with men (GBMSM) experience marginalization, discrimination and violence due to their sexual orientation and same-sex sexual activity [1][2][3], which may negatively impact physical, mental, and sexual health outcomes [4,5]. The minority stress model posits that the prejudice, discrimination, and stigma experienced by sexual and gender minority individuals-as a result of sexual or gender identity-contributes to higher levels of stress, which may lead to mental health problems [6] and sexual risk behaviors [7,8].Prior studies have found high levels of mental health problems (i.e.…”
Section: Introductionmentioning
confidence: 99%